«The universals of culture» as ontological problem - Dareskyi, Vitaliy (Actual Problems of Mind, 2017)
The paper investigates the ontological dimensions of the «universals of culture» in the context of modern philosophy and theory of culture. The author considers the concept of «cultural universals» as a collection of fundamental principles, underlying the interrelations between personality, the Other and the world.